Experimental and analytical investigation of geo-grid confined RC beams with glass fiber reinforced concrete. (December 2021) - Joel Shelton, J; Venkata Naresh, Y; Arun Solomon, A; Daniel, C
Abstract: The application of geosynthetics in infrastructure is an innovative development in concrete with the usage of geo-grid. In the plastic hinge region of Reinforced Concrete (RC) beams the additional shear reinforcement was provided by using glass fibers. The present study is carried out for the RC beam specimens, in which the additional shear confinement was given by geo-grid of various sizes was studied. In RC beams, less labor work only needed for the confinement and with the usage of geo-grid and also for the confinement the usage of geo-grid will be an effective solution. The effect of geo-grid with the glass fiber reinforced concrete has also been investigated by experimental observations and non-linear finite element simulations. Detailed 3D non-linear finite element analyses with perfect bonding of RC beam confined with geo-grid in ANSYS was carried out. One conventional beam, one conventional beam with glass fiber and three beams with a different configuration of geo-grid and volume of glass fiber were casted. For studying load–deflection behaviour, the single point loading was carried out for the geo-grid specimens and conventional beam specimens under flexure. Depend upon the usage of glass fibers and geo-grid confinement in the beam specimens, the experimental test results show that there is an enhancement in the post-yield behaviour and strength. The flexure test on beam specimens reveals that the strength of the geo-grid and its size plays a vital role in improving the load-deformation behaviour as well as crack propagation. The load–displacement behaviour and damage predicted from finite element analysis almost agree with the experimental result. Hence geo-grid seem to be an alternative material which having great ductile behaviour for the strengthening of RC beam.